County‐Level Hispanic Ethnic Density and Cardiovascular Disease Mortality. Issue 19 (2nd October 2018) - Rodriguez, Fatima; Hu, Jiaqi; Kershaw, Kiarri; Hastings, Katherine G.; López, Lenny; Cullen, Mark R.; Harrington, Robert A.; Palaniappan, Latha P.
Abstract : Background: Hispanics are the fastest growing ethnic group in the United States, and little is known about how Hispanic ethnic population density impacts cardiovascular disease (CVD) mortality. Methods and Results: We examined county‐level deaths for Hispanics and non‐Hispanic whites from 2003 to 2012 using data from the National Center for Health Statistics' Multiple Cause of Death mortality files. Counties with more than 20 Hispanic deaths (n=715) were included in the analyses. CVD deaths were identified using International Classification of Diseases, Tenth Revision (ICD‐10), I00 to I78, and population estimates were calculated using linear interpolation from 2000 and 2010 census data. Multivariate linear regression was used to examine the association of Hispanic ethnic density with Hispanic and non‐Hispanic white age‐adjusted CVD mortality rates. County‐level age‐adjusted CVD mortality rates were adjusted for county‐level demographic, socioeconomic, and healthcare factors. There were a total of 4 769 040 deaths among Hispanics (n=382 416) and non‐Hispanic whites (n=4 386 624). Overall, cardiovascular age‐adjusted mortality rates were higher among non‐Hispanic whites compared with Hispanics (244.8 versus 189.0 per 100 000). Hispanic density ranged from 1% to 96% in each county. Counties in the highest compared with lowest category of Hispanic density had 60% higher Hispanic mortality (215.3 versus 134.2 per 100 000 population). In linear regression models, after adjusting for county‐level demographic, socioeconomic, and healthcare factors, increasing Hispanic ethnic density remained strongly associated with mortality for Hispanics but not for non‐Hispanic whites. Conclusions: CVD mortality is higher in counties with higher Hispanic ethnic density. County‐level characteristics do not fully explain the higher CVD mortality among Hispanics in ethnically concentrated counties.